Impact of transition risks of climate change on Chinese financial market stability - An, Qiguang; Zheng, Lin; Li, Qingzhao; Lin, Chengwei (Frontiers in Environmental Science, 2022)
The transition risks caused by climate change are becoming a hot issue in the field of finance research. In this paper, we firstly construct the transmission mechanism of "climate change–change in investor attention–financial stability" and analyze the impact of transition risks on Chinese financial market stability. Secondly, we construct a Climate Change Index (CCI). The CCI depicts changes in investors’ attention to transition risks of climate change based on the Baidu Index. We also use the dynamic factor model (DFM) to construct a Financial Stress Index (FSI) that describes Chinese financial market stability. The FSI can also effectively identify financial events within the sample interval. Then, we use the TVP-VAR model to empirically analyze the impact of the transition risks of climate change on Chinese financial market stability. We present the following results: In short and medium terms, more financial market pressure will be caused by the increase of the CCI. In the long run, it is uncertain for the impact of the increase of CCI on Chinese financial market pressure. Finally, we present valuable countermeasures and suggestions from different perspectives of investors, financial institutions and regulators.